Communicative Language Teaching in rural classrooms: Students’ and pre-service teachers’ experiences - Chango PalateCarol Aracelly; Núñez CoelloKatia Masherly; Arias ArroyoPaulina Alexandra; Abata ChecaFanny Mercedes (Revista UTCiencia: i-ISSN: 1390-6909. e-ISSN: 2602-8263, 2023)
The traditional teaching methods have proven to be ineffective, demonstrating a low English level, especially,inmarginalizedzones.Asaresult,CommunicativeLanguageTeaching(CLT)hasbeen proposed to improve student’s learning English. The aim of the study was to describe the students’ and pre-service teachers’ experiences in implementing the CLT method in rural classrooms. The participants were twenty-three pre-service teachers from the Pedagogy of National and Foreign Languages Major at Technical University of Cotopaxi and two hundred fifty students belonging to parishes and neighborhoods in Cotopaxi, Ecuador. A qualitative-descriptive research design was employed, and data was collected through teachers’ diaries and students’ exit slips. The thematic analysis was used to analyze the participants’ excerpts. The results showed that the application of adequate strategies and attractive didactic material according to students’ levels and interests enable learners to implement appropriately CLT and develop their communicative competence .Additionally, the Encounter, Clarify, Remembering, Internalize, and Fluently Use (ECRIF) lesson planning framework was useful to organize the CLT method in the classroom since it enhances language skills from the simplest to complex activities to produce the language.